The persistence of hardship over the life course - Thomas L. Hungerford (Levy Economics Institute of Bard College, 2002)
This paper focuses on the persistence of hardship from middle age to old age. Proposed status maintenance models suggest that stratification of economic status occurs over the life course (e.g., little mobility is seen within the income distribution). Some studies have found evidence to support this, but none have looked at broader measures of well-being. Using 29 years (1968-96) of data from the Panel Study of Income Dynamics (PSID), the author employs hypothesis tests (t-tests) and logistic regression techniques to examine the relationship between middle-age chronic hardships and adverse old-age outcomes. In almost every case, individuals who experience middle-age chronic hardships are significantly (statistically) more likely to experience adverse old-age outcomes.
Keywords: 330